Dealing With the Body Shaming Phenomenon in Cyberspace: Prevention and Challenges in Law Enforcement - Dewi Bunga (International Journal of Research in Community Services, 2022)
Body shaming is one of the verbal crimes that exist in cyberspace. According to the Clarity Clinic, body shaming is the act of humiliating someone based on their body shape by mocking them. Launching the official website of the Association of Anorexia Nervosa and Associated Disorders, body shaming is any act or practice of insulting other people's body shape or size, weight, hairstyle, dress and appearance. In this study, two problems will be discussed, namely 1) why body shaming act needs attention in criminal law policies and 2) how criminal law policies deal with body shaming. This research is a normative juridical research that examines legal norms regarding body shaming in Indonesia. Legal materials consist of primary and secondary legal materials collected through literature study. The analysis was carried out qualitatively. Body parts are used as objects to drop a person's image. Body shaming is a form of bullying or bullying. Practices like this can leave severe emotional trauma and disrupt the victim's mental health. The trauma experienced by the victim can even occur in the long term. This form of bullying can be carried out by the closest people such as parents, relatives, friends, strangers, to negative comments on social or conventional media. Body shaming act in cyberspace is a challenge in criminal law policy in Indonesia, both in the context of prevention and in law enforcement policies against perpetrators. Digital literacy is a very important pillar to understand that mocking someone's body shape is a crime.